Data Assimilation for Wave Data in Persian Gulf Using WAVEWATCH-III Spectral Model - Hamidreza Moazzami (نشریه مهندسی دریا, 2017)
The major problems in modeling of different oceanographic and meteorological parameters are limitations in numerical methods and human incomplete knowledge in physical processes involved. As a result, significant differences between the results of these models and in situ observations of these parameters might exist. One of the powerful solutions for decreasing the forecast errors in the models is to use data assimilation technique. In this study the optimal interpolation data assimilation method is employed which is based on statistical rules. Moreover, the quick Canadian method is used to optimize the data assimilation method used in model. Model assessment is performed by comparison between running wave model with and without using data assimilation and SAR wave data in Persian Gulf. It shows that using data assimilation in WAVEWATCH-III model reduces the error in wave height predictions significantly.